2014
DOI: 10.1016/j.rser.2014.05.007
|View full text |Cite|
|
Sign up to set email alerts
|

A review of methods to match building energy simulation models to measured data

Abstract: Whole building energy simulation (BES) models play a significant role in the design and optimisation of buildings. Simulation models may be used to compare the cost-effectiveness of energy-conservation measures (ECMs) in the design stage as well as assessing various performance optimisation measures during the operational stage. However, due to the complexity of the built environment and prevalence of large numbers of independent interacting variables, it is difficult to achieve an accurate representation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
319
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(356 citation statements)
references
References 60 publications
1
319
0
3
Order By: Relevance
“…A detailed review of the calibration techniques for building simulation can be found elsewhere (Coakley et al 2014;Fabrizio and Monetti 2015). The calibration can be conducted with either deterministic or probabilistic method.…”
Section: Stochastic Building Energy Models For Individual Buildingsmentioning
confidence: 99%
“…A detailed review of the calibration techniques for building simulation can be found elsewhere (Coakley et al 2014;Fabrizio and Monetti 2015). The calibration can be conducted with either deterministic or probabilistic method.…”
Section: Stochastic Building Energy Models For Individual Buildingsmentioning
confidence: 99%
“…According to Coakley et al (2014), calibration approaches for building energy simulation can be broadly defined as either manual or automated.…”
Section: Current Calibration Approachesmentioning
confidence: 99%
“…Calibration approaches that fall under this category typically requires the energy modeler to perform iterative manual tuning (Reddy, 2006;Coakley et al, 2014) and to have in-depth knowledge of the building and its operation. Therefore, manual calibration approaches usually involve either 1) detailed energy audits to gain a better understanding of the building systems and their operations (Ian Shapiro, 2009;Pedrini et al, 2002;Yoon et al, 2003); 2) intrusive tests where groups of end-use loads are turned on and off in a controlled sequence to provide information on their end-use impact (Soebarto, 1997); 3) collection of high-resolution and high-quality data for empirical validation (Clarke et al, 1993); or 4) a protocol of short-term end-use monitoring to gather data that would help explain the differences between measured and simulated data (Subbarao, 1988;Manke et al, 1996).…”
Section: Manual Calibration Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…These tools are widely used for analyzing energy consumption and determining heat load of the buildings [21][22][23][24][25][26]. Boyano et al [25] studied energy demand and potential savings in buildings based on simulation results.…”
Section: Introductionmentioning
confidence: 99%